Sustainable strategies for Tierra Bomba Island based on the concept of main ecological structure (2019)
The research carried out aims to provide territorial environmental management of the joint execution between the State, the Academy and the Communities as a result of a management model based on sustainability strategies, formulated from the application, in a local insular domain, of the concept of Main Ecological Structure (MES), and taking as a case study the island Tierra Bomba. The proposed sustainability strategies seek, from the natural resources and social interactions, to guide the actions of preservation, restoration, sustainable use and productive activities, based on the biophysical elements that are part of the MES of the Island for participating in the development of its social and ecological function. These are also being negatively affected in terms of quality, extension and connectivity, fundamentally due to inadequate urban expansion processes, with the consequent increase in the extension and magnitude of the constructions present in the littoral and on the continental soil and the reduction of the borders between urban settlements and the biomes of the Island.